Bioherbicidal Assessment of Aqueous Extracts of Mesquite (Prosopis juliflora) on Weeds Control and Growth, Yield and Quality of Wheat - SHAH,R.H. (2018)
ABSTRACT: Two-year field experiments were conducted to investigate the phytotoxicity of mesquite (Prosopis juliflora) on weed control and yield of wheat in 2013-14 and 2014-15. Mesquite aqueous extracts were prepared with 10, 20, 30 and 40% concentration of leaves, stems, and roots and were compared with tap water (control). These experiments were laid out in a completely randomized block design with four replications. All parameters (weed density, fresh weed biomass, dry weed biomass, chlorophyll content, leaf area index, leaf area duration, crop growth rate, net assimilation rate, plant height and number of tillers) were significantly reduced by applying the mesquite extracts. Among different concentrations, the maximum level (40%) of all three plant parts of mesquite subsequently reduced the study parameters including weed density, fresh and dry weed biomass, leaf area index, leaf area duration, crop growth rate, net assimilation rate, chlorophyll contents, plant height, number of tillers, spike length, number of grains, 1000-grain weight, grain yield, biological yield, harvest index and grain protein content. On the basis of the results, it is concluded that aqueous extracts of mesquite may contain many phytotoxic substances which can negatively affect the growth and yield of agricultural crops; therefore, wheat should not be planted close to mesquite.